SURFACE ACTIVITY AND STABILIZING ABILITY OF NEW BIOLOGICAL SURFACTANTS - Makhkamov R.; Saidkulov F.; Samandarov Sh.; Makhkamova I.; Nurmanova M. (Journal Park Publishing, 2023)
Biosurfactants are surface-active molecules produced by microorganisms and offer several advantages including low toxicity, high biodegradability, remain active at extreme pH and salinity. These potential advantages make them useful in several applications such as ecofriendly construction mixtures, health care products, cosmetics, food and oil industries. Currently, industrial and residential construction is developing rapidly, and this requires the manufacture of concrete structures of increased strength, high reliability and durability. In this regard, a very urgent problem is the creation of cement-concrete compositions with good rheological and structure-forming properties. To effectively solve these problems, it is necessary to widely use special plasticizing surfactant additives for cement mixtures. The purpose of this work is to investigate colloidal chemical properties of new biological surface-active substances depending on the concentration and temperature, and their effectiveness for disperse systems equilibration. Different methods for the measurements of properties and efficiency of new biosurfactants were used. The effects of concentration and temperature on the surface-activity and foaming abilities of new biological surface-active substances were studied. It has been established that with an increase in the concentration of biosurfactants and the temperature of the system, the surface activity and stabilizing ability of new biosurfactants were increased. The effect of new biosurfactants on the technological properties of cement slurries was studied. It has been shown that, at low concentrations, the retarding effect of new biosurfactants increases linearly with an increase in their concentration and surface activity. In this case, the formation of biosurfactant adsorption layers leads to a decrease in the hydration of cement particles. It has been established that at high concentrations adsorption of biosurfactant aggregates on the cement surface occurs, which leads to increased stability of the dispersion and a sharp decrease in the setting rate of the cement mass. By choosing the concentration of biosurfactant additives, it was possible to control the setting time and strength of cement stone, which can be used in the production of cement-concrete compositions and building materials.
Keywords: surfactants, surface activity, foam-forming ability, adsorption, disperse systems, plasticizing effect.